Analysis of risk factors for depression and anxiety in women with polycystic ovary syndrome - Yang, Yanting; Liu, Lin; Hu, Ning; Huo, Huyan; Yang, Xin; Wang, Fang (Frontiers in Global Women's Health, 2025)
BackgroundPolycystic ovary syndrome (PCOS) is one of the most common reproductive endocrine disorders among women of reproductive age, often accompanied by a series of symptoms such as hirsutism, hair loss, menstrual disorders and obesity, resulting in an increasing risk of depression and anxiety in such patients.MethodsA total of 413 patients in the Reproductive Medicine Center of the Second Hospital of Lanzhou University from June 2021 to June 2023 were enrolled. We collected sociodemographic information and lifestyle-related factors using a structured questionnaire. Patient Health Questionnaire (PHQ-9) and Generalized Anxiety Disorder Scale (GAD-7) were used to evaluate the psychological status of the subjects. Sleep-related variables were assessed using the Pittsburgh Sleep Quality Index (PSQI), and metabolic measures were collected from patients' medical records.ResultsCompared with the control group, PCOS patients were younger, the average age was (27.39 ± 3.48) years old, and the BMI value was higher, the difference was statistically significant (p < 0.05). The proportions of depression and anxiety in PCOS patients were 47.7% and 39.9%, respectively. In PCOS patients with depressive anxiety symptoms, the proportions of mild, moderate, moderately severe and severe depression were 31.6%, 12.4%, 1.6% and 2.1%, respectively. The proportions of mild, moderate, moderately severe and severe anxiety were 30.6%, 6.2%, 1.0% and 2.1%, respectively. Depression was significantly associated with serum free triiodothyronine (FT3) OR (95% CI) = 3.33 (1.30–8.55), sleep duration 4.99 (1.45–17.23) and daytime dysfunction 8.24 (3.53–19.22). Anxiety was significantly associated with daytime dysfunction OR (95% CI) = 3.45 (1.78–6.70). No association was found between mental health and other metabolic characteristics in PCOS patients (p > 0.05).ConclusionAccording to the results of the current study, a high proportion of women with PCOS have mental health disorders, and there is a significant correlation between mental health disorders and sleep conditions.